The nurse practitioner ethicist: Distinct from a nurse ethicist? - Kay, Jesse Michael (Nursing ethics, 2025)
Ethics has been central to the nursing profession. Challenges in patient care have arisen through advances in medicine through science and technology. These advances have led to patients being sustained in ethically difficult situations. Nurses have uniquely witnessed both the suffering of patients and rendered care for extended periods of time at the bedside. Through these caring relationships nurses have developed expertise in advocating for their patients. Many nurses have also returned to graduate school to develop their nursing science and ethical reasoning. Recently, the field of nursing has developed the role of the nurse ethicist. Nurse ethicists often also work as clinical ethics consultants. Additionally, nursing has advanced to include nurse practitioners as advanced practice nurses. Nurse practitioners have also obtained additional education in ethical reasoning and are working in roles similar to nurse ethicists and clinical ethicists. Given the science and nature of the nurse practitioner there may be unique facets to nurse practitioners who are ethicists. To date there are no proposals for nurse practitioner ethicists. Let this be the first proposal addressing the distinctions of the nurse practitioner ethicist.